Analysis of the Ki-67 index in the vaginal epithelium of castrated rats treated with tamoxifen (Clinics, 2016)
OBJECTIVES: Vaginal atrophy and breast cancer are common conditions in postmenopausal women and tamoxifen is the standard endocrine treatment for hormone-sensitive tumors. The present study aimed to assess the effect of tamoxifen on Ki-67 protein expression in the vaginal epithelium of castrated rats. MATERIAL AND METHODS: Forty Wistar-Hannover adult, virgin, castrated rats were randomly divided into two groups, group I (control, n=20) and group II (tamoxifen, n=20), receiving 0.5 ml of propylene glycol and 250 µg of tamoxifen diluted in 0.5 ml of propylene glycol, respectively, daily by gavage for 30 days. On the 31st day, the rats were euthanized and their vaginas were removed and fixed in 10% buffered formalin for the immunohistochemical study of Ki-67 protein expression. Data were analyzed by the Levene and Student’s t tests (p